Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In course of solving the problem How to show that $\lim \sup a_nb_n=ab$ I feel that I've probably made some mistake in my solution for I didn't use the fact that $a_n>0$ $\forall$ $n\geq1.$

Please help me to find out the mistake I've made:

  • $\exists$ a subsequence $\{a_{r_n}\}$ of $\{a_n\}$ such that $a_{r_n}\to a.$ Now $a_{r_n}\to a, b_{r_n}\to b\implies a_{r_n}b_{r_n}\to ab\implies ab$ is a subsequencial limit of {$a_nb_n$}. If possible let $\exists$ a subsequence $\{a_{p_n}b_{p_n}\}$ of $\{a_nb_n\}$ such that $a_{p_n}b_{p_n}\to m>ab.$ Since $b_n,b>0$ so $b_n^{-1}\to b^{-1}>0$ whence $a_{r_n}\to mb^{-1}>a,$ a contradiction to $\lim \sup a_n=a.$ Hence the result follows.

Thanks for voting up the question. But that didn't actually eliminate my confusion. I'm looking for some concrete comments and opinions.

share|improve this question
    
What are the definition of $a$ and $b$? –  Wayson Kong Jan 10 '13 at 13:31
    
$a=\lim\sup a_n,b=\lim b_n.$ Follow the link given in the question. –  Sugata Adhya Jan 10 '13 at 13:35
    
why not try using the definition of Cauchy sequence? –  Santosh Linkha Jan 10 '13 at 13:43
    
@experimentX: Is the definition I used wrong? –  Sugata Adhya Jan 10 '13 at 13:47
    
In the original problem math.stackexchange.com/questions/275093/… the existence of $\lim_{n\to\infty} b_n$ was not assumed. Your assumption is much stronger, since without it you cannot conclude the convergence of $a_{p_n}$ from the convergence of $a_{p_n}b_{p_n}$. –  ACARCHAU Jan 11 '13 at 3:43

2 Answers 2

up vote 0 down vote accepted

You do need some extra assumption. Consider the following example (where $a$ is a finite real):

$a_n=a$ if $n$ is odd, $a_n=-n$ if $n$ is even,

$b_n=-1.$ (so in notation, $\lim b_n=b=-1$)

Then lim sup of $a_n$ is $a$, and lim $b_n$ is b, yet we have

$a_nb_n=-a$ if $n$ is odd, $a_nb_n=n$ if $n$ is even.

So in this example the limsup of $a_nb_n$ is $+\infty$, whereas $ab$ is not.

EDIT: I noted that in your proof you needed to use $b>0$ but that assumption should be stated in the problem.

share|improve this answer

Your proof is correct. You proved that:

If $\lim\sup a_n=a, \ \lim b_n=b>0$ then $\lim\sup a_nb_n=ab$.

which is true.

The assumptions $a_n>0$ and $b_n>0, \ \forall n\geq1$ are required for this proposition:

If $\lim\sup a_n=a, \ \lim\sup b_n=b$ then $\lim\sup a_nb_n=ab$.

Also see the last corollary here.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.